2016
DOI: 10.1103/physrevd.93.125010
|View full text |Cite
|
Sign up to set email alerts
|

Rényi entropy of a free (2, 0) tensor multiplet and its supersymmetric counterpart

Abstract: We compute the Rényi entropy and the supersymmetric Rényi entropy for the six-dimensional free (2, 0) tensor multiplet. We make various checks on our results, and they are consistent with the previous results about the (2, 0) tensor multiplet. As a by-product, we have established a canonical way to compute the Rényi entropy for p-form fields in d-dimensions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 48 publications
8
41
0
Order By: Relevance
“…(5.9), (5.12) give the correct known values of the a and c Weyl anomaly coefficients in d = 4 [60] and in d = 6 [3] and the values of C T also agree with the general expression for C T,d (ψ) given in (1.13). The expressions for the Rényi entropy agree with [38,47].…”
Section: Jhep06(2017)002supporting
confidence: 69%
See 1 more Smart Citation
“…(5.9), (5.12) give the correct known values of the a and c Weyl anomaly coefficients in d = 4 [60] and in d = 6 [3] and the values of C T also agree with the general expression for C T,d (ψ) given in (1.13). The expressions for the Rényi entropy agree with [38,47].…”
Section: Jhep06(2017)002supporting
confidence: 69%
“…footnote 11) and thus the two free energies may a priori differ by a Weyl-anomaly term. It was observed that for fields with gauge invariance S 1 computed on S 1 q × H d−1 is not automatically proportional to the Weyl anomaly a-coefficient (see [45,46] for 4d vectors and [47] for 6d antisymmetric tensors), but one can achieve this by shifting F q by a constant (that may be interpreted as an edge mode contribution).…”
Section: Jhep06(2017)002mentioning
confidence: 99%
“…This quantity was computed on the gauge theory side and for free field theories where an agreement was explicitly demonstrated for the free energies computed for both S 3 q and S 1 q × H 2 [12]. In [17] both the nonsupersymmetric and the supersymmeric Renyi entropies are computed for the abelian M5 brane on S 1 q × H 5 and the generalization of the supersymmetric Renyi entropy to the nonabelian M5 brane was obtained in [18] and more generally to the nonabelian (1,0) SCFT's in [19].…”
Section: Introductionmentioning
confidence: 89%
“…where S(q) U (1) is the abelian Renyi entropy that was computed in [12,13] and H(q) is a cubic polynomial in γ = 1/q whose explicit form was found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Let us now obtain this result in a different way that we will later generalize to the nonabelian case as well. We use the result for the abelian Renyi entropy [12]…”
mentioning
confidence: 99%